Upaya Manajemen Kinerja Strategis Perusahaan Melalui Sistem Informasi Pemeliharaan Aset Bergerak Berbasis Web - Abigail Athallah, Muhammad; Kraugusteeliana, K; Muhammad Abigail Athallah; K Kraugusteeliana (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim : This research aims to design a web-based movable asset maintenance information system as a company's effort to implement strategic performance management. Design/Method/Approach : This research method uses the Software Development Life Cycle (SDLC) method with the use of the waterfall model. In addition, the analysis and design of the system in this research uses the Unified Modeling Language (UML), the PIECES method to identify problems, and Blackbox Testing as a test of the suitability of the system's functionality. Research Finding : The results of this study indicate that the functional requirements of the web-based movable asset maintenance information system are following the company's functional requirements based on testing through black box testing. Theoretical contribution/Originality : This research is expected to increase knowledge in the field of web-based information system design technology. Practitionel/Policy implication : The implementation of strategic performance management through a web-based movable asset maintenance information system has an impact on the digital transformation of the company's activity procedures, the performance of the company's activity procedures which is increasing, data management is carried out centrally, the negative impact of security is reduced, and excellent service is increasing. Research limitation : The object of the research is in the Pertamina Patra Niaga, Sultan Syarif Kasim II Pekanbaru Aircraft Filling Depot. In addition, this research is limited to the design of a web-based movable asset maintenance information system.